Suppressing of slow magnetic relaxation in tetracoordinate Co(II) field-induced single-molecule magnet in hybrid material with ferromagnetic barium ferrite - Nemec, Ivan (Sci Rep, 2015)
The novel field-induced single-molecule magnet based on a tetracoordinate mononuclear heteroleptic Co(II) complex involving two heterocyclic benzimidazole (bzi) and two thiocyanido ligands, [Co(bzi)(2)(NSC)(2)], (CoL4), was prepared and thoroughly characterized. The analysis of AC susceptibility data resulted in the spin reversal energy barrier U = 14.7 cm(−1), which is in good agreement with theoretical prediction, U(theor.) = 20.2 cm(−1), based on axial zero-field splitting parameter D = −10.1 cm(−1) fitted from DC magnetic data. Furthermore, mutual interactions between CoL4 and ferromagnetic barium ferrite BaFe(12)O(19) (BaFeO) in hybrid materials resulted in suppressing of slow relaxation of magnetization in CoL4 for 1:2, 1:1 and 2:1 mass ratios of CoL4 and BaFeO despite the lack of strong magnetic interactions between two magnetic phases.